Lifebuoy Soap Stock Decision Making System Of Neighbourhood 5 And 6 Pagar Dewa Urban Village Bengkulu - Ujang Juhardi; Yulia Darmi; Dedy Abdullah; Fiqi Muttaqin Septa Nugraha (Penerbit Jurnal Indonesia, 2022)
A product provider must make the right decisions in predicting the amount of new stock that will be distributed to stalls. Sales of lifebuoy soap in Neighbourhood OF 5 and 6 experienced a difference in the number of sales each month. This of course will make it difficult for the supplier of goods to know the exact number of products that must be stocked. To be able to overcome this and increase the realization of sales from each stall, it is necessary to have a fast and appropriate prediction process that can overcome problems in determining the amount of distribution of new stock. The method used is the Fuzzy Tsukamoto method and is written in the PHP programming language. Where this method is chosen because it is a method of counting with variable words, instead of counting with numbers, human expert systems can be implemented into machine language easily and efficiently. Identification of user needs is needed in the design to determine what features can be used in the system and use story boards to get an overview of the system. System testing using black box by testing all buttons on the application. Based on the results of the study, it can be concluded that this system helps simplify and shorten the time in determining the amount of fulfillment of new stock requests